El ánima sola : Enrique Buenaventura adapta a Tomás Carrasquilla - Fernández, Carolina Ramos (Acta Hispanica, 2010)
The Colombian playwright Enrique Buenaventura adapted for the scene the story of qualified Tomás Carrasquilla “The alone soul”. It is not the first time that the first one adapts to the second one so his pieces: In the God’s righthand side father, The Guariconga (inspired by the work Palonegro); San Antoñito also they inspired also by the work of the novelist, taking it as a point of item for his theatrical theory. In all the cases, Enrique Buenaventura searches, in Tomás Carrasquilla’s work, the popular voice, the autochthonous speech, the known topic and the direct communication with the spectators and spectators of his epoch. Ingredients with which it re-elaborates the popular history opening new points of view, renewing prominent figures and introducing new characters without interferences.